Form v. substance in Islamic banking and financial transactions - Saleem, Muhammad Yusuf (2008)
This paper focuses on issues of form and substance in Islamic banking and financial transactions. The paper critically examines the argument that compares Islamic banking products with permissible (halal) foods, islamically slaughtered chickens, and properly concluded marriages. The paper argues that these comparisons are misleading and cannot be maintained. It argues that a transaction establishes a certain contractual relationship between the parties and entitles them to certain rights and obligations. This paper concludes that issues related to substance in transactions are directly concerned with the rights and obligations of the contracting parties. A transaction that in form complies with the Shari’ah but not in substance has consequences for the contracting parties. It may entitle the contracting parties to a set of rights and obligations different from the ones that are intended by the Shari’ah. It concludes that a transaction that complies in words and forms with the Shari’ah but deprives the parties of their rights and obligations cannot be defended on procedural grounds.